Enhancing Capacity and Stability of Anionic MOFs as Electrode Material by Cation Exchange - Akintola, Oluseun; Gerlach, Patrick; Plass, Christian T.; Balducci, Andrea; Plass, Winfried (Frontiers in Chemistry, 2022)
In this study we report on the characterization and use of the anionic metal-organic framework (MOF) JUMP-1, [(Me2NH2)2[Co3(ntb)2(bdc)]]n, alongside with its alkali-metal ion-exchanged analogs JUMP-1(Li) and JUMP-1(Na), as electrode materials for lithium and sodium batteries. Composite electrodes containing these anionic-MOFs were prepared and tested in 1M lithium bis(trifluoromethylsulfonyl)imide (LiTFSI) in propylene carbonate (PC) and/or 1M sodium TFSI (NaTFSI) in PC. We showed that the ion-exchanged materials JUMP-1(Li) and JUMP-1(Na) display higher capacities in comparison with the original as-prepared compound JUMP-1 (490 mA∙h∙g−1 vs. 164 mA∙h∙g−1 and 83 mA∙h∙g−1 vs. 73 mA∙h∙g−1 in Li and Na based electrolytes, respectively). Additionally, we showed that the stability of the electrodes containing the ion-exchanged materials is higher of that of JUMP-1, suggesting a form of chemical pre-alkalation works to stabilize them prior to cycling. The results of these studies indicate that the use of designed anionic-MOF represents a promising strategy for the realization of high performance electrodes suitable for energy storage devices